Pemberdayaan Penyandang Disabilitas Fisik Melalui Pelatihan Vokasional pada Program Rehabilitasi Sosial - Dinah Pangestuti (Jurnal Kewidyaiswaraan, 2021)
Abstract This article describes the empowerment of physically disabled people through vocational training. The main problems faced by disabled people are that they have very limited skills and are dependent on others. Moreover, they are commonly still in the productive age group, so they need to be guided, nurtured, empowered, and given ooprtunity to develop their potentials. The objectives were describing the implementation process of empowerment of the physically disabled through vocational training, finding supporting and inhibiting factors, and determining the institution’s solution. The informants were determined purposefully. The data collection was performed by interview. The data collected from documents related with empowerment and the collected data were analyzed qualitatively. The present article showed that empowerment is a process of developing the physically disable from a powerless state into powerful state. Services in the institution are limited because with changes in the society, regulations and policies from the Ministry of Social affairs, social services shifted from “charity-based” to citizen rights, from “institutional-based” to “family/community-based”. Similarly, the service model of social rehabilitation changed. However, it was undeniable that some service aspects still encountered obstacles which affected service performance, including to: a. the Institution, to be more focused on recruitment comprehensive data mapping should be performed first before socialization or registration of potential beneficiaries, so that quantitatively higher number of potential beneficiaries could be covered. Moreover, the quality and quantity of the recruitment should be improved and coverage in other areas where recruitment had never been performed should be increased. Meanwhile, empowerment for the physically disabled shouldn’t only be focused on improving knowledge and work skills, but also change of attitudes and behaviors of the beneficiaries. b. Assessors as the main assets of the institution didn’t have social work background and competency as assessor. The current systemic assessment ran well by assessing physiological, psychological, sociological and vocational aspects, but it should be supported by standard and equipment, and more professional assessors, before using work sample method if the assessors couldn’t reveal beneficiary’s capacity using the measurement. Keywords: Physically Disabled; Training; Empowerment.